2011
DOI: 10.1007/s00253-011-3508-8
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic biodecolorization mechanism of methyl orange by Shewanella oneidensis MR-1

Abstract: In this work, we investigated the anaerobic decolorization of methyl orange (MO), a typical azo dye, by Shewanella oneidensis MR-1, which can use various organic and inorganic substances as its electron acceptor in natural and engineered environments. S. oneidensis MR-1 was found to be able to obtain energy for growth through anaerobic respiration accompanied with dissimilatory azo-reduction of MO. Chemical analysis shows that MO reduction occurred via the cleavage of azo bond. Block of Mtr respiratory pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 34 publications
4
65
0
1
Order By: Relevance
“…Since the boiling point of 4-aminobenzenesulfonic acid exceeded the temperature limit of the GC-MS, only N,N-dimethyl-p-phenylenediamine was detected in the GC chromatogram. From the MS analysis, the main fragmentation ions (m/z) were 136, 121, 105, 93, 77, 60, 40 and 18 which were comparable with other researchers in the N,N-dimethyl p-phenylenediamine determination (Parshetti et al, 2010;Cai et al, 2012;Chen et al, 2008).…”
Section: Degradation Pathwaysupporting
confidence: 64%
See 1 more Smart Citation
“…Since the boiling point of 4-aminobenzenesulfonic acid exceeded the temperature limit of the GC-MS, only N,N-dimethyl-p-phenylenediamine was detected in the GC chromatogram. From the MS analysis, the main fragmentation ions (m/z) were 136, 121, 105, 93, 77, 60, 40 and 18 which were comparable with other researchers in the N,N-dimethyl p-phenylenediamine determination (Parshetti et al, 2010;Cai et al, 2012;Chen et al, 2008).…”
Section: Degradation Pathwaysupporting
confidence: 64%
“…The initial stage of degradation proposed to be the azo bond cleavage which caused the disappearance of absorbance peak at 460 nm with respect to time. Symmetric cleavage of this azo bond tends to the formation of the N,N-dimethyl p-phenylenediamine and 4-amino sulfonic acid (Parshetti et al, 2010;Cai et al, 2012). The N,N-dimethyl p-phenylenediamine was obtained from GC-MS analysis at the retention time 13.395 min.…”
Section: Degradation Pathwaymentioning
confidence: 99%
“…The decolorization ability of C. saccharolyticus observed in this study is comparable to that of Shewanella oneidensis MR-1 [10] and Pseudomonas luteola [26], which had strong ability of decolorization in previous researches. MO (100 mg/L) was removed completely in $7 h by S. oneidensis MR-1.…”
Section: Decolorization Of Mo By C Saccharolyticussupporting
confidence: 87%
“…The results of earlier studies suggested the reduced flavins generated by flavin reductases are responsible for the unspecific reduction of azo dyes [7]. And a recent study suggested the electron transport chain of MtrAMtrB-MtrC might be a major avenue for delivering electrons from the outer membrane surface to the azo dyes [10]. There is no report, however, on how the hydrogenase is involved specifically in the dye decolorization process [8].…”
Section: Introductionmentioning
confidence: 96%
“…The multi haem cytochromes MtrF, OmcA, and OmcB may fulfill a function as terminal dye reductase. Furthermore, azo dye decolorization studies have been carried out with MR-1 gene knock-out mutant strains by Yu's group in details recently (Cai et al 2012;Cao et al 2013). It was found that the block of the Mtr pathway resulted in 80 % decrease of the decolorization rate.…”
Section: Direct Bacterial Decolorizationmentioning
confidence: 98%